Bedside Teaching Consistently Improves Clinical Competence and Critical Thinking in Nursing Education - Yasnida Rosy; Kristina Lisum (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Professionalism and nursing competence are fundamental pillars in ensuring high‑quality and safe patient care. However, a persistent gap between academic theory and clinical practice continues to hinder the optimal development of clinical competence, critical thinking, and nurses’ decision‑making abilities. Although bedside teaching has been widely recognized as an effective instructional method globally, its implementation varies considerably, influenced by workload demands and the competency of clinical facilitators. This study aims to identify and critically analyze the impact of bedside teaching on improving nurses’ clinical competence based on empirical evidence from national and international studies. A systematic review approach was employed, guided by the PRISMA framework. Literature searches were conducted across multiple electronic databases, including Google Scholar, ScienceDirect, SpringerLink, MDPI, EBSCOHost, ClinicalKey, ClinicalKey Nursing, Sage Journals, ProQuest, and PubMed, focusing on articles published between 2020 and 2025. A total of 15 articles that met the inclusion criteria were selected and comprehensively analyzed. The review process followed rigorous and systematic steps, including critical appraisal. Analysis of the 15 studies revealed that bedside teaching consistently enhances clinical competence and critical thinking skills by up to 35%. Approximately 80% of the studies reported that bedside teaching is more effective than conventional learning methods. Its effectiveness is attributed to direct reflection, real‑time feedback, and collaborative learning approaches. However, challenges such as high workload and limited time continue to affect its implementation. In conclusion, bedside teaching is an effective, contextual, and relevant clinical learning strategy for strengthening the professional competence of nurses and nursing students across various healthcare settings. To optimize its implementation, institutional commitment is required through structured training for clinical instructors and systematic integration of bedside teaching into nursing education curricula.Keywords: bedside teaching; clinical nurse competence; clinical learning